A Comparative Study of Fe (II) Ion Adsorption onto Chemically Activated Banana Peel and Sawdust Bio-adsorbent - Shrestha, Suman Lal (International Journal of Applied Sciences and Biotechnology, 2018)
The adsorption capacity of ferrous ions onto bio-sorbents prepared from two different types of bio-waste of banana peel (CABP) and sawdust (CASD) treated with sulfuric acid was studied using Langmuir and Freundlich isotherms. Result shows that the optimum pH value for about 99 % Fe (II) adsorption onto the CABP and CASD was found to be 3 and 4, respectively, after 5 hours or more contact time period. Both the Langmuir and Freundlich adsorption models are fitted to remove the Fe (II) ions from aqueous solution by the bio-adsorbent of CABP and CASD. The maximum adsorption capacities for the CABP and CASD were found to be about 34 and 116 mg/g, respectively. These results showed that the CASD seems to be more effective bio-adsorbent than the CABP to remove the Fe (II) ions from drinking or/and wastewaters. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 137-141